From Tradition to Transition: Living Values Across Generations - Bhattarai , Tikaram (GS WOW: Wisdom of Worthy Research Journal, 2025)
Cooperation and respect are foundational societal values that shape interpersonal relationships and community cohesion. This study explores how these values have transformed, deteriorated, and eroded across multiple generations. To examine changes in attitudes and behaviors related to cooperation and respect over time within a society. Using a narrative inquiry approach, 18 participants from three age groups (13–19, 20–59, and 60+) were interviewed to capture generational perspectives on these values. Findings reveal that cooperation and respect have evolved due to social dynamics, cultural shifts, and technological advancements. Traditional expressions of respect based on customs and physical gestures have given way to more superficial and expedient forms, especially among younger generations. Similarly, cooperation has shifted from deeply communal practices to more individualistic and transactional interactions influenced by industrialization and rising individualism. Older generations tend to pass down less emotional but more enduring forms of these values, while conventional cooperative and respectful behaviors are increasingly replaced by impersonal and mechanical interactions. The study highlights the erosion of fundamental social values amid rapid societal change, offering critical insights into the implications for future generations and the transformation of core cultural principles.